Seasonal activity of the Denali caribou herd, Alaska - Boertje, Rodney D. (Rangifer, 1985)
Activity of female and young caribou in the Denali herd was studied from June 1978 through April 1980 to help assess the food availability/nutritional status of this reduced population. No nutritional stress was evident as inferred by the greater activity of Denali caribou in late winter compared with starving caribou in West Greenland and by the low proportion of time spent grazing in spring compared with reindeer on overgrazed ranges in Norway. Also, low proportions of time were spent running from insects due to relatively few insects and a high availability of insect-relief sites. A low proportion of time was spent cratering due to windswept conditions. Activity budgets calculated from complete active-rest cycles and accompanied by the duration of active and rest periods may be useful indicators of relative food availability/nutritional status, particularly in late winter/early spring. Duration of active periods is presumably most strongly related to rumen fill, and, thus, food availability. Duration of rest periods was not significantly different among seasons (P<0.05), except when insects, rutting bulls, and, presumably, mushroom-searching altered active-rest cycles.Sesongmessige svingninger av aktiviteten i Denali karibu-flokk, Alaska.Abstract in Norwegian / Sammendrag: Aktiviteten hos simler og ungdyr i Denali karibouflokk ble studert fra juni 1978 til utgangen av april 1980 som hjelpemiddel for å bestemme næringstilbud/ernæringsstatus i denne reduserte karibustamme. Ingen ernæringsmessig stress var åpenbar, noe som kan utledes av den større aktivitet hos Denali karibu på senvinteren sammenlignet med sultende karibu i Vest-Grønland samt den lave andel av beiting sammenlignet med rein på overbelastede beiter i Norge. Videre ble en lav andel av tiden brukt til å rømme fra insekter, fordi insektplagen var relativt liten og at det var lett adgang til områder der dyrene kunne befri seg fra insektene. Graving krevde også liten andel av tid takket være vindblåste snøforhold. Aktivitetsbudsjetter beregnet ut fra totale aktivitets-/hvilesykluser kan være nyttige indikatorer på relativ næringstilbud/ernæringsstatus, særlig på senvinter og tidlig vår. Varigheten av aktive perioder er sannsynligvis mest knyttet til vomfylde og, derfor, til næringstilbud eller næringstilgjengelighet. Varigheten av hvileperioder var ikke signifikant forskjellig mellom sesonger (P<0.05), unntatt når insekter, brunstige bukker og, sannsynligvis også, soppsøking forandret aktivitet-/hvilesykluser.